2010
DOI: 10.1007/s13197-010-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative enzymatic profile of mushrooms stored at low temperature

Abstract: Fruiting bodies of 6 mushrooms including Agaricus bisporus, Hyspizygus ulmarius, Pleurotus florida PF-01, Pleurotus florida PF-01 R5, Pleurotus platypus and Pleurotus sajor-caju PSC-04 were analyzed for antioxidative enzymatic profile during low temperature storage. Colour, rehydration ratio and moisture were taken as indices of accessing their shelf-life/marketability, of which, colour contributed significantly while rehydration ratio and moisture did not change considerably during storage. Mushrooms were sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…Similarly, the variety, Umran exhibited three POX isozymes from 0 to 6th d of storage (Fig. 2b) and thereafter, upto 10th d, there were only two major bands of POX, while Kaithali had two POX isozymes throughout the storage period The number of SOD and POX isoenzymes observed during the present investigations was less than that observed by Dama et al (2010) who found 4 to 6 SOD isoforms and 2 to 4 POX isoforms in six different accessions of mushroom stored at 5 and 10°C. The difference observed in SOD and POX isozymes was in terms of intensity and size of bands and apparently no new addition or deletion of isozymes occurred throughout the storage.…”
Section: Resultscontrasting
confidence: 40%
“…Similarly, the variety, Umran exhibited three POX isozymes from 0 to 6th d of storage (Fig. 2b) and thereafter, upto 10th d, there were only two major bands of POX, while Kaithali had two POX isozymes throughout the storage period The number of SOD and POX isoenzymes observed during the present investigations was less than that observed by Dama et al (2010) who found 4 to 6 SOD isoforms and 2 to 4 POX isoforms in six different accessions of mushroom stored at 5 and 10°C. The difference observed in SOD and POX isozymes was in terms of intensity and size of bands and apparently no new addition or deletion of isozymes occurred throughout the storage.…”
Section: Resultscontrasting
confidence: 40%
“…The postharvest senescence of fresh products is often associated with increased oxidative damage to proteins, lipids and nucleic acids by reactive oxygen species (ROS) (Dama et al 2010 ; Li et al 2016 ; Mittler 2002 ). ROS were considered toxic by-products of aerobic metabolism, which were disposed of using antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Antioxidative enzymatic profile of six mushrooms stored at low temperature was analysed (Dama et al 2010). India with its vast reserve of lignocellulosic waste, predominantly subtropical climate (20-30°C) and cheap labor is specially suited for the cultivation of species like Pleurotus.…”
Section: Introductionmentioning
confidence: 99%